2020
DOI: 10.1117/1.jbo.25.4.046005
|View full text |Cite
|
Sign up to set email alerts
|

Reliability assessment for blood oxygen saturation levels measured with optoacoustic imaging

Abstract: Significance: Quantitative optoacoustic (OA) imaging has the potential to provide blood oxygen saturation (SO 2 ) estimates due to the proportionality between the measured signal and the blood's absorption coefficient. However, due to the wavelength-dependent attenuation of light in tissue, a spectral correction of the OA signals is required, and a prime challenge is the validation of both the optical characterization of the tissue and the SO 2 .Aim: We propose to assess the reliability of SO 2 levels retrieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Furthermore, the spectral unmixing step is conducted on a per-pixel basis and is thus vulnerable to motion artifacts, which may be further emphasized by noise due to vessel reactivity. For this reason, several motion correction algorithms have been recently introduced (31,32). Further, a recent study showed that MSOT provided consistent and reproducible functional soft tissue characterization, independent on the investigating personnel (33).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the spectral unmixing step is conducted on a per-pixel basis and is thus vulnerable to motion artifacts, which may be further emphasized by noise due to vessel reactivity. For this reason, several motion correction algorithms have been recently introduced (31,32). Further, a recent study showed that MSOT provided consistent and reproducible functional soft tissue characterization, independent on the investigating personnel (33).…”
Section: Discussionmentioning
confidence: 99%
“…The fluence ϕ is dependent on unknowns such as the absorption and scattering in the tissue surrounding x 0 . Quantitative OA imaging methods either depend on model-based inversion [2][3][4][5][6][7] or data-driven approaches. [8][9][10][11][12][13] These approaches perform well in silico but often struggle with the translation to real measurements in phantoms or in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…There the fluence φ is dependent on unknowns like the absorption and scattering in the tissue surrounding x 0 . qPAI methods either depend on model-based inversion [2][3][4][5][6][7] or data-driven approaches. [8][9][10][11][12][13] These approaches often perform well in silico but struggle with the translation to real measurements in either phantoms or in vivo.…”
Section: Introductionmentioning
confidence: 99%